Traditional Chinese Medicine Decoction Combined With Antipsychotic for Chronic Schizophrenia Treatment: A Systematic Review and Meta-analysis - Shi, Xiao-Jie; Fan, Fang-Cheng; Liu, Hua; Ai, Yang-Wen; Liu, Qing-Shan; Jiao, Yu-Guo; Cheng, Yong (Frontiers in Pharmacology, 2021)
Despite several studies suggesting the effectiveness of traditional Chinese medicine (TCM) in schizophrenia, there is still a lack of systematic summary and analysis on the role of TCM as adjuvant therapy in chronic schizophrenia. For this purpose, we conducted a meta-analysis to study the efficacy of TCM as an adjuvant combined with antipsychotics in the treatment of chronic schizophrenia. Until April 2020, based on the review of 6 electronic databases, 8 articles were selected. The articles compared TCM decoction assisted antipsychotic therapies with an antipsychotic alone in the treatment of chronic schizophrenia by analyzing a total of 810 cases. The results showed that TCM combined with antipsychotics have beneficial effects on the Positive and Negative Syndrome Scale (PANSS), including the changes in total score, negative score, and the clinical effects evaluated by the PANSS scale. Subgroup analysis showed that the effects of auxiliary TCM with different efficacy on the positive and psychopathological scores were significantly different. It was found that adjuvant treatment with TCM can reduce some side effects and improve the patient's living conditions in the evaluation of the Schizophrenia Quality Of Life Scale (SQLS). Many studies have proved that TCM is safe and well-tolerated. Although the difficulties of using limited TCM remains to be generalized, it still has great potential in the adjuvant treatment of chronic schizophrenia.